Facilitators for the development and implementation of health promoting policy and programs – a scoping review at the local community level. (December 2016) - Weiss, Daniel; Lillefjell, Monica; Magnus, Eva
Abstract Background Health promotion, with a focus on multidimensional upstream factors and an ecological, life-course approach, is establishing itself as the guiding philosophy for addressing public health. Action at the political and programmatic level on the Social Determinants of Health has proven effective for promoting and building public health at all levels but has been particularly evident at the national and international levels – due in large part to available documents and guidelines. Although research and experience establish that health promotion is most effective when settings-based, the development of health promoting policies and programs at the local level is still difficult. This study intended to investigate available knowledge on the development and implementation of health promoting policies and programs at the local level and identify factors most important for facilitating capacity building and outcome achievement. Methods We used a scoping review in order to review the current literature on local policy development and program implementation. Keywords were chosen based on results of a previous literature review. A total of 53 articles were divided into two categories: policy and implementation. Critical analysis was conducted for each article and a summary assembled. Data was charted with specific focus on the aims of the study, data acquisition, key theories/concepts/frameworks used, outcome measures, results, and conclusions. Results The articles included in this study primarily focused on discussing factors that facilitate the development of health promoting policy and the implementation of health promotion programs. Most significant facilitators included: collaborative decision-making, agreement of objectives and goals, local planning and action, effective leadership, building and maintaining trust, availability of resources, a dynamic approach, a realistic time-frame, and trained and knowledgeable staff. Within each of these important facilitating factors, various elements supporting implementation were discussed and highlighted in this study. Conclusion Our results indicate that clear and consistent facilitators exist for supporting health promoting policy development and program implementation at the local level. These results offer a starting point for local action on the Social Determinants of Health and have the potential to contribute to the development of a framework for improving action at the local level.